2017
DOI: 10.15294/kemas.v13i2.12069
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Knowledge and Attitude Regarding DHF with PSN Behavior Among the Community Around the Campus

Abstract: The city of Semarang as the capital of Central Java province is a DHF endemic city and has a high risk of dengue fever. Based on data from Central Java Provincial Health Office in 2015, DBD IR from 2012 to 2015 has increased. Dengue Hemorrhagic Fever (DHF) in the work area of Puskesmas Sekaran, Gunungpati in 2013 there are 7 cases of DHF patients, the highest number of Dengue fever is in Sukorejo Village with 6 patients then followed by Kelurahan Sekaran with 1 patient. The purpose of this study is to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Based on the empirical evidence there were still many people who did not keep the environment clean, including outside or inside their house. Moreover, based on the evidence, the link between knowledge and attitude or knowledge and behavior showed that there was no significant difference (Pujiyanti, Pratamawati and Trapsilowati, 2016;Kurniawan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the empirical evidence there were still many people who did not keep the environment clean, including outside or inside their house. Moreover, based on the evidence, the link between knowledge and attitude or knowledge and behavior showed that there was no significant difference (Pujiyanti, Pratamawati and Trapsilowati, 2016;Kurniawan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…DHF is a disease caused by a virus from the Flaviviridae family transmitted through mosquito bites (arthropod-borne viruses/ arbovirus), namely Aedes aegypti and Aedes albopictus mosquitoes, and can cause mortality if not seriously taken care of (Kurniawan et al, 2017;Wang et al, 2020). DHF has clinical manifestations of fever, and muscle or joint pain, accompanied by leukopenia, rash, lymphodenopathy, and thrombocytopenia (Patel et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Terutama perilaku ibu yang memiliki motivasi tinggi dalam pemberantasan sarang nyamuk berdarah dengue diharapkan mampu memberikan contoh yang baik kepada ibu yang kurang memiliki motivasi dalam pemberantasan sarang nyamuk berdarah dengue melalui kegiatan 3M [30] . Masyarakat memiliki peran yang cukup penting mengeliminasi vektor sebagai langkah utama dalam upaya memutus rantai penularan untuk mencegah munculnya kasus di masa depan [31] .…”
unclassified